Landscape and variation of RNA secondary structure across the human transcriptome - Wan, Yue; Qu, Kun; Zhang, Qiangfeng Cliff; Flynn, Ryan A.; Manor, Ohad; Ouyang, Zhengqing; Zhang, Jiajing; Spitale, Robert C.; Snyder, Michael P.; Segal, Eran; Chang, Howard Y. (Nature (London), 2014)
An RNA secondary structure (RSS) map of coding and noncoding RNA from a human family (two parents and their child) is produced; this reveals that approximately 15% of all transcribed single nucleotide variants (SNVs) alter local RNA structure, and these SNVs are depleted in certain locations, suggesting that particular RNA structures are important at those sites. Probing the in vivo RNA structurome Being single-stranded, RNA can adopt a diversity of secondary structures via inter- and intramolecular base-pairing. Three studies published in this issue of Nature provide an in-depth view of the variety, dynamics and functional influence of RNA structures in vivo . Sarah Assmann and colleagues map the in vivo RNA structure of over 10,000 transcripts in the model plant Arabidopsis thaliana . Their struc-seq (structure-seqence) approach incorporates in vivo chemical (DMS) probing and next-generation sequencing to provide single-nucleotide resolution on a genome-wide scale. Distinct patterns of structure are found to be correlated with coding regions, splice sites and polyadenylation sites. Comparison of these results with those obtained by earlier technologies reveals that, although predictions for some classes of genes were fairly accurate, others, such as those involved in stress response, were poorly predicted and may reflect changes that made them more adapted to that condition. Jonathan Weissman and colleagues have also developed a DMS-seq method to globally monitor RNA structure to single-nucleotide precision in yeast and mammalian cells. Comparing their findings with in vitro data, the authors conclude that there is less structure within cells than expected. Even thermostable RNA structures can be denatured in cells, highlighting the importance of cellular processes in regulating RNA structure. Howard Chang and colleagues asked a different question: how does RNA secondary structure change on a transcriptome-wide level in related individuals? By calculating the RNA secondary structures of two parents and their child, they find that about 15% of transcribed single-nucleotide variants affect local secondary structure. These 'RiboSNitches' are depleted in certain locations, suggesting that a particular RNA structure at that site is important. This study illustrates that there is much to be learned about how changes in RNA structure, particularly as imparted by genetic variation, can alter gene expression. In parallel to the genetic code for protein synthesis, a second layer of information is embedded in all RNA transcripts in the form of RNA structure. RNA structure influences practically every step in the gene expression program 1 . However, the nature of most RNA structures or effects of sequence variation on structure are not known. Here we report the initial landscape and variation of RNA secondary structures (RSSs) in a human family trio (mother, father and their child). This provides a comprehensive RSS map of human coding and non-coding RNAs. We identify unique RSS signatures that demarcate open reading frames and splicing junctions, and define authentic microRNA-binding sites. Comparison of native deproteinized RNA isolated from cells versus refolded purified RNA suggests that the majority of the RSS information is encoded within RNA sequence. Over 1,900 transcribed single nucleotide variants (approximately 15% of all transcribed single nucleotide variants) alter local RNA structure. We discover simple sequence and spacing rules that determine the ability of point mutations to impact RSSs. Selective depletion of ‘riboSNitches’ versus structurally synonymous variants at precise locations suggests selection for specific RNA shapes at thousands of sites, including 3′ untranslated regions, binding sites of microRNAs and RNA-binding proteins genome-wide. These results highlight the potentially broad contribution of RNA structure and its variation to gene regulation.